Double Row Rotator Cuff Repair for Massive Reparable Rotator Cuff Tear - Stephen Marcaccio MD; Rafael Buerba MD/MHS; Justin Arner MD; James Bradley MD (Video Journal of Sports Medicine)
Background: Massive rotator cuff tears, defined as those that involved 2 or more tendons or where the length of the greatest diameter is greater than 5 cm, present a unique surgical challenge as there can be significant scarring, retraction, and poor tissue quality. Furthermore, healing of these tears is less reliable. This video presents our technique for anatomic, double row repair of a massive reparable rotator cuff tear. Indications: Indications for operative intervention include acute traumatic tears, as well as patients with pain and weakness who have failed to respond to conservative management, including physical therapy with confirmed large full thickness rotator cuff tear on advanced imaging. Of note, findings such as glenohumeral osteoarthritis, advanced muscle atrophy (Goutalier III/IV), superior migration of the humeral head >7 mm, and tears larger than 40 mm in length and width are concerning for irreparable tears, and may represent contraindications to surgical repair. Technique Description: The patient is placed in the lateral decubitus position. After diagnostic arthroscopy is performed, a subacromial bursectomy is performed. A radiofrequency probe and arthroscopic shaver are used to perform releases in the subacromial space as well as superior to the glenoid. Preparation of the footprint of the humeral head is then performed to create a good healing surface. The rotator cuff is grasped to confirm tension free mobilization. The medial row anchors are then placed. Once placed, the sutures are incorporated into 2 lateral row anchors in sequential fashion. Subacromial decompression is then performed. Results: Reduced pain and improved shoulder function are the goals of treatment, with sling immobilization lasting for roughly 6 weeks postoperatively prior to initiating strengthening and range of motion protocols. Discussion/Conclusion: Arthroscopic double row repair produces an anatomic and stable reduction of reparable massive rotator cuff tears for patients that have failed conservative management. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.